Pemberdayaan Ekonomi Masyarakat Di Kelompok Madu Langkapura: Implementasi Bank Sampah - Margaretta Indarti, Sahaji; Riani, Novi; Rahmahwaty (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
Waste is a troubling problem in many countries, including Indonesia, with its impact that extends to various aspects of life. The amount of waste continues to increase along with changes in people's consumption behavior. In this context, the implementation of waste banks emerges as a solution for managing waste and empowering the community's economy. Community economic empowerment is an effort to strengthen and improve their economic potential. A waste bank is a waste management system that facilitates the collection, sorting, and sale of waste with the aim of reducing waste and providing economic benefits to the community. The research used a field research approach with qualitative methods. Data were obtained through interviews, observations, and related documents. Data analysis is descriptive and interpretative. The implementation of the Waste Bank in the Langkapura Honey Group increases community awareness about waste management, empowers the economy, and improves financial literacy. The Waste Bank is not only a place for collecting waste but also an education and empowerment center. The implementation of the Waste Bank in the Langkapura Honey Group succeeded in changing the community's view of waste into an economic source and providing financial benefits. Active education about waste and financial literacy are the keys to success. Suggestions include increased socialization, operational efficiency, collaboration, periodic evaluation, and further research.